Hypothetical Learning Trajectory: Bagaimana Perannya dalam Pembelajaran Matematika di Sekolah Dasar? - Chindy Novelin Lantakay; Patrisia Pasu Senid; Irna Karlina Sensiana Blegur; Damianus. D Samo (Griya Journal of Mathematics Education and Application, 2023)
In today's modern era, students are required to become learning centers. Thus, students must have prior experience and knowledge in order to be able to connect with the next concept (material). However, because the differences between the nature of elementary schooler and mathematics, teacher needs to structure learning that can be a bridge to neutralize these differences. One way to structure the learning is make a learning design such as Hypothetical Learning Trajectory (HLT). HLT is an alleged learning process as an anticipation of things that might happen, both students' thinking processes and other things in the learning process. The term HLT refers to the teacher's lesson plan which is designed not only to consider the material, but also the level of understanding, knowledge and student characteristics of the material being studied, so that students experience the learning process from the beginning to achieving the expected mathematics learning goals for students. This article is a literature study that aims to discuss HLT in elementary mathematics learning.